Highly photostable zinc selective molecular marker bearing flexible pivotal unit: opto-fluorescence enhancement effect and imaging applications in living systems1. Issue 20 (28th May 2015) - Sinha, Sougata; Gaur, Pankaj; Dev, Sagarika; Mukherjee, Trinetra; Mathew, Jomon; Mukhopadhyay, Subhrakanti; Ghosh, Subrata
<x xml:space="preserve">Abstract</x> Zinc selective molecular probe with remarkable photostability is demonstrated.